Optimizing an Appropriate Sterilization Procedure to Control Microbial Contamination during In vitro Culture of Piper longum L. - Talukdar, Nizu Moni; Dutta, Dibakar; Mitra, Shawon; Sony, Sonia Khan; Haider, Ishita; Sultana , Tania; Das, Subroto K (Plant Tissue Culture and Biotechnology, 2025)
Piper longum L., a unisexual perennial climber, is well-known for its high therapeutic potential, but is becoming threatened due to overharvest. The bioactive compounds, responsible for its medicinal properties, are also considered a favorable niche for microorganisms. The persistent contamination caused by these endophytes is the major challenge in micro-propagation. The present study aimed to develop an optimized protocol to reduce microbial contamination by maintaining a high level of regeneration capacity of the cultured explants. For this purpose, eight types of surface sterilization methods and four different antimicrobial agents were used in callus induction media. Among various surface sterilization methods, treatment T3 showed the minimum level of contamination with a comparatively higher level of explant survivability. In case of antimicrobial agent, the highest effectiveness in controlling contamination with high potential of callus induction capacity was observed in MS media supplemented with 3.0 mg/l 2,4-D and 25 mg/l carbendazim (M1). In this medium composition the rate of contamination elimination was 82.33% and rate of response in callus induction was 44.67%. Thus, the composition of T3 sterilization methods and carbendazim as antimicrobial agent can be a suitable procedure to mitigate microbial contamination in Piper longum tissue culture by ensuring improved culture viability and regeneration potential. Plant Tissue Cult. & Biotech. 35(1): 117-128, 2025 (June)